2015
DOI: 10.1007/s40610-015-0026-y
|View full text |Cite
|
Sign up to set email alerts
|

Osteocytes and Skeletal Pathophysiology

Abstract: For many years, osteocytes have been the forgotten bone cells and considered as inactive spectators buried in the bone matrix. We now know that osteocytes detect and respond to mechanical and hormonal stimuli to coordinate bone resorption and bone formation. Osteocytes are currently considered a major source of molecules that regulate the activity of osteoclasts and osteoblasts, such as RANKL and sclerostin; and genetic and pharmacological manipulations of either molecule markedly affect bone homeostasis. Besi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 103 publications
0
40
0
1
Order By: Relevance
“…The discrepancy may be a consequence of the relatively young age of the mice used in our study. It is worth noting that other studies have also found that serum levels of sclerostin do not always correlate with Sost skeletal gene expression, which may reflect distinct paracrine and endocrine functions of sclerostin . After treatment, there is an increase in both the gene expression and circulating levels of sclerostin, demonstrating positive feedback in response to the antibody.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The discrepancy may be a consequence of the relatively young age of the mice used in our study. It is worth noting that other studies have also found that serum levels of sclerostin do not always correlate with Sost skeletal gene expression, which may reflect distinct paracrine and endocrine functions of sclerostin . After treatment, there is an increase in both the gene expression and circulating levels of sclerostin, demonstrating positive feedback in response to the antibody.…”
Section: Discussionmentioning
confidence: 81%
“…Limitations of this study include the use of relatively young, growing animals, where sclerostin levels are expected to be lowest . Despite the low circulating sclerostin levels, Scl‐Ab treatment improved several XLH‐related pathologies in young Hyp mice.…”
Section: Discussionmentioning
confidence: 98%
“…Although initially described as inactive quiescent cells buried in the mineralized tissue, osteocytes are essential for the accomplishment of the functions of the skeleton. Osteocytes coordinate bone acquisition during growth, control the maintenance of a healthy skeleton suit for locomotion, and provide protection of essential organs . Osteocytes orchestrate the work of osteoblasts that form bone and osteoclasts that resorb it by producing and secreting factors in response to environmental cues, thus adapting the skeleton to mechanical needs and hormonal changes.…”
Section: Osteocytes: Challenges and Opportunities To Study Their Rolementioning
confidence: 99%
“…A small proportion (<20%) of osteoblasts on bone surfaces become surrounded by the matrix proteins that they produce, and differentiate into osteocytes . Osteoblast–osteocyte differentiation is characterized by alterations in gene expression and is accompanied by morphological and functional cellular changes . During osteocytogenesis, the cuboidal shape of the highly secretory osteoblasts progressively changes to a star‐like morphology that characterizes the osteocytes.…”
Section: Osteocytes: Challenges and Opportunities To Study Their Rolementioning
confidence: 99%
“…These actions are controlled by osteocytes, differentiated osteoblasts embedded in the bone matrix [7]. Cell-to-cell communication via gap junctions among these cells was first appreciated in morphological studies using electron microscopy [8].…”
Section: Connexins and Pannexins In Bonementioning
confidence: 99%